1988
DOI: 10.1017/s004740450001294x
|View full text |Cite
|
Sign up to set email alerts
|

The context of oral and written language: A framework for mode and medium switching

Abstract: This article demonstrates that our descriptions of orality and literacy – from the traditional dichotomy to the more recent continuum – are inadequate, largely because they are grounded in the Western positivist tradition and use as their typical texts casual conversation and academic writing. The introduction of a new medium of communication, the computer, into the workplace clearly demonstrates that medium of communication is itself a linguistic choice, depending on the context of situation. The article pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(43 citation statements)
references
References 11 publications
1
39
0
3
Order By: Relevance
“…The answers of the participants display variability since some of them consider it easy while other found it somewhat difficult. Research has shown that people encounter difficulties when writing emails to those perceived as higher in status when initiating communication, suggesting new ideas, making request, and expressing disagreement or criticism (Baron, 1998(Baron, , 2000Kling, 1996, Murray, 1988.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The answers of the participants display variability since some of them consider it easy while other found it somewhat difficult. Research has shown that people encounter difficulties when writing emails to those perceived as higher in status when initiating communication, suggesting new ideas, making request, and expressing disagreement or criticism (Baron, 1998(Baron, , 2000Kling, 1996, Murray, 1988.…”
Section: Discussionmentioning
confidence: 99%
“…Email writers' ambivalence and uncertainty about how to encode communicative intent in this text-only medium tend to surface especially in hierarchical relationships, such as between students and faculty, and in situations involving impositions on the addressee (Biesenbach-ucas, 2007). While students can write to their peers in any manner, they feel uneasy to write emails to superiors (Baron, 1998;2000;Murray, 1988;as cited in Chen, 2006. Students may be temporarily "unaware" of whom they are addressing in emails which results in language that lacks status congruence (Herring, 2002;Sproull & Kiessler, 1986;1991).…”
Section: Introductionmentioning
confidence: 99%
“…The features that characterise this discourse on, for example, IRC have led researchers to posit that CMC occupies a position on a continuum between doi: 10.5842/33-0-25 spoken and written language (Murray 1988;Baron 1998Baron , 2000. The data examined in this study suggest that this also holds for Afrikaans CMC.…”
Section: Differences Between Cmc and Spoken And Traditional Written Lmentioning
confidence: 99%
“…Daft and Lengel 1984;Kahai and Cooper 2003). As a so-called 'lean' medium, email has been considered suitable mainly for simpler forms of communication (Murray 1988;Bälter 1998), while issues that may involve conflict, negotiation and more complex discussions are seen to be more difficult to resolve via email. This perspective on email and other text-based digital media has been related to the lack of communicative cues participants have been shown to remain in experiments, regardless of the medium.…”
Section: Research On Email In Organizations and Workplacesmentioning
confidence: 99%